Achieving synergy enhancement of strength and ductility in Ti-6Al-2Sn-4Zr-2Mo-0.1Si alloy by fabricating a new multiscale microstructure. (15th March 2023) - Zhou, Yu; Wang, Ke; Wen, Xin; Xin, Renlong; Wang, Jingfeng; Liu, Qing
Abstract: A new multiscale microstructure (NMM) comprised of long-plate α (αlong ) grain, fine-equiaxed α (αfine ) grain and ultrafine α (αultra ) precipitates was fabricated by hot rolling and aging treatment on a bimodal microstructure (BM) of Ti-6Al-2Sn-4Zr-2Mo-0.1Si (Ti6242s) alloy. Interestingly, the aging arouses a synergy enhancement of strength and ductility in NMM. The αlong and αfine grains mainly contribute to ductility, while the αultra and retained dislocations mainly promote strength. Moreover, the cooperation among multiscale α grains generates an apparent hetero-deformation induced (HDI) stress to improve strength and ductility simultaneously. Graphical abstract: Image, graphical abstract